How does the evolution of an organization's multiple-dominant-logic system affect its ambidextrous innovation?. Issue 3 (22nd February 2021) - Lin, Haifen; Qu, Tingchen
Abstract : Purpose: This paper aims to address how an organization's multiple-dominant-logic system evolves as it grows and how does this evolution affect the way managers choose to balance ambidextrous innovation. Design/methodology/approach: This paper adopts an interpretive and exploratory case study on the mechanism of how the multiple-dominant-logic system influences the decision of balanced ambidextrous innovation. Considering that the multiple-dominant-logic system will change with the development of a firm, this paper focuses on exploring how the evolution of multiple-dominant-logic system affects the way managers choose to balance ambidextrous innovation. The authors spent almost two years collecting data from M-grass Ecology and following the evolution and innovation through semi-structured interviews, archival data and observation. Then they set up a framework showing the influence mechanism by analyzing the data through a four-step process. Findings: This research points out that an organization's multiple-dominant-logic system may change for several times in its growth. It provides a model for the evolution of a multiple-dominant-logic system. It confirms that firms' multiple-dominant-logic system is not immutable, but evolves with the change of the firm's internal resources and external environment. Also, it finds that under the influence of different multiple-dominant-logic architectures, mangers choose different ways to balance ambidextrous innovation. In this process, appropriate entrepreneurial bricolage plays a significant role in balancing ambidextrous innovation. Originality/value: The findings offer some valuable insights for further research on dominant logics and ambidextrous innovation and hold important implications for managers making a decision.